Digital Mobility of Financial Capital Across Different Time Zones, Factor Prices and Sectoral Composition - Biswajit Mandal (Global Labor Organization (GLO), 2024)
In this paper I make an effort to formalize the possibility of transfer of financial capital across time zones to exploit the benefit of day night mismatch between two countries. The major precondition for such transaction is the completion of production, buying and selling of the product in twelve hours day-time of any calendar date. And the process of monetary transaction must be done through digital platform. In this backdrop I argue that exploration of such possibility reduces the effective cost of capital in the sector which is potentially timezone difference exploitative. Subsequently we find other factor price effects and sectoral composition changes in a very conventional Heckscher-Ohlin nugget kind of structure. Though the results are not very surprising, the mechanism through which it works is very unconventional. Without any traditional channels like trade, FDI, technology transfer, endowment changes I generate price effect due to digital mode of payment and twelve hours of activity.
Keywords: F12; F16; F21; 330; Time Zone Differences; Service Trade; Financial Capital; Outsourcing